The Application Of Good Governance Principles For Performance Improvement Of Uluale Sub-District Office Apparatuses - Muhammad Rais Rahmat Razak; Sailan Manan; Arismunandar Arismunandar; Lutfiah Jafar; Rifdan Rifdan (AIBPM Publisher, 2022)
Performance-based organizations are the demands of the people as they are eager to get maximum services from the government. Thus, to ensure the high performance of the state apparatus, especially those who serve in sub-district offices, the support of good governance is necessary. This study aims to investigate the effect of good governance on sub-district apparatus performance. This research applied a quantitative descriptive method with a sample size of 92 people selected from 1201 heads of households. The research was conducted in Uluale Sub-District, Watangpulu District, Sidenreng Rappang Regency. The results showed that the application of the principle of good governance and apparatus performance was included in the category of